Durum wheat grain and pasta from locally-grown crops: a case-study on Saragolla (Triticum turgidum ssp. turanicum) and Senatore Cappelli (Triticum turgidum ssp. durum) wheats - Acquistucci, Rita; Melini, Valentina; Galli, Vincenzo (Emirates Journal of Food and Agriculture, 2020)
The ancient grains Senatore Cappelli and Saragolla are often used as raw material, generally in mixture, for the production of pasta, which represents one of the most consumed foods in Italy. Due to the wide employment of these wheats in cereal based foods, it was found interesting to get information on the nutritional value of food as widespread as pasta made by means of such wheats. In this study, long and short pasta samples produced from Saragolla and Senatore Cappelli were considered. Proximate chemical composition, starch digestibility and antioxidant compounds as well as cooking properties were studied. When the optimum cooking time is applied, pasta presents good sensory characteristics also thanks to the high protein content of raw material. Moreover, the employment of the durum whole meal in the pasta production, also guarantees a good level of bioactive compounds such as phenolic compounds.